Benign inflammatory cervical smear in a background of normal diagnostic dilatation and curettage finding - A rare presentation of endometrial carcinoma - Shalihin, Mohd Shaiful Ehsan; Harun, Zulkifli; Osman, Iskandar Firzada (2017)
Endometrial carcinoma is a primary tumor of the uterus that usually presented with abnormal uterine bleeding commonly in post menopausal woman. However, it can also manifests as abnormal cervical cytology even in a pre-menopausal age group which should be confirmed by endometrial biopsy. Dilatation and curettage (D&C) is an invasive and diagnostic procedure to identify specific causes for abnormal uterine bleeding with high sensitivity of up to 99% in detecting endometrial lesions. We report a case of early detection of endometrial carcinoma in a 56 year old diabetic woman who presented with history of intermitted prolonged menses which previously reassured with a normal diagnostic dilatation and curettage finding. However, subsequent cervical smear as part of routine screening in our clinic revealed persistent benign inflammatory changes. Despite in dilemma of previous normal D&C, we referred again this case for bedside endometrial biopsy which revealed a new finding of endometrial carcinoma. She benefits early staging and treatment. We would like to report a case of a rare presentation of early endometrial carcinoma manifested as incidental findings of benign inflammatory cervical changes in a low suspicious patient in view of clear findings of a recent diagnostic D&C. This case had proved important role of continuous regular screening in primary care regardless of previous diagnostic background.